DEVELOPMENT OF X-BAND RADAR DATA-BASED SNAKELINE FOR PREDICTING SEDIMENT DISASTER - Henggar Risa Destania; Istiarto Istiarto; Rachmad Jayadi (Simposium II UNIID 2017, 2017)
Sediment-related disaster are terrible disaster that can catastrophically impact to facilities and people must to keep in mind to make sediment-related disaster information that can be predicted from rainfall and response of drainage area by using snakeline. This research produce the important indices on precipitation related to debris and shows current status of the stage of response of drainage area against rainfall by using a couple of short and long term indices. It shows the water storage volume in soil layer with calculation of soil water index (SWI) by using X-band MP (Multi Parameter) rainfall radar data that has been installed at the top of Merapi Mountain (Merapi Museum). The snakeline can be used as monitoring and observation tools of SWI changes in response to rainfall intensity in Boyong river (BO-D5) and works as a database for the next research in identifying criteria for warning. Although there was no record of sediment disaster occurrence, at least from the result of snakeline it was confirmed that from June 2016 – June 2017 with 80.28 mm SWI maximum values has not yet become the maximum limit of SWI value for lahar occurrence in Boyong drainage area (BO-D5).